Pengaruh Pemberian Ekstrak Biji Mahoni (Swietenia mahagoni Jacq.) terhadap Penurunan Kadar Alanin Transaminase Mencit (Mus musculus) yang Diinduksi Parasetamol - Aflifia Birruni Sabila; R.P. Andri Putranto; . Martini (Nexus Biomedika, 2013)
Background: Seeds of Swietenia mahagoni Jacq. contain various antioxidants such as alkaloids, saponins, flavonoids, triterpenoids, steroids, and tannins. They are thought having hepatoprotector effect. This study aimed to know the influence of Swietenia mahagoni Jacq. to decrease alanin transaminase level in paracetamol-induced mice. Methods: Samples were 25 male mice, Swiss webster strain, 2-3 months old and + 25 g of weight, each. Samples were divided into 5 groups, each group consisted of 5 mice. Group K(-) were administered aquadest, while group K(+) were administered curcuma with the dose of 25 mg/25 g body weight of mice for 14 days. Group P1, P2 and P3 were consecutively administered mahagony seed extract with the dose of 0 mg, 14 mg and 28 mg/25 g body weight of mice for 14 days. Paracetamol was administered to groups of K(+), P1, P2, and P3 on the 12th, 13th, and 14th day. On the 15th day, blood samples were taken and the ALT (alanine transaminase) level was measured with a Model 902 Automatic Analyzer Hitachi. Data were analyzed by the Kruskal-Wallis test (? = 0.05) and Post Hoc Mann Whitney test (? = 0.05). Results: Mean rate of alanine transmainase of group K(-), K(+), P1, P2 and P3 was 54.04 7.74 U/L; 46.74 3.33 U/L; 173.5 39.445 U/L; 88.90 37.04 U/L and 73.18 7.46 U/L, consecutively Conclusions: There was correlation between the oral administration of mahagony seed extract (Swietenia mahogany Jacq.) and the decrease of alanin transaminase level in paracetamol-induced mice. Keywords: Alanin Transaminase (ALT), Seed extract of Swietenia mahagony Jacq.,